Governing the Economic Transition: How Taiwan Transformed its Industrial System to Attain Virtuous Cycle Development - Wong, C.Y.; Hu, M.C.; Shiu, J.W. (Wiley, 2015)
This study explores the transitional processes of Taiwan's innovation system over the past half century, evolving from being rooted in traditional industries to attaining development in a virtuous cycle of development. Our approach is inspired by the Arena of Development theory and acknowledges the system of transformation failures, in which we highlighted the types of failures that might impede economic progress and how they were overcome in the evolutionary targeting of Taiwan's industrial development. Our findings demonstrate that the success of Taiwan's economic transition is targeted on, and evolves with, a series of macrolevel policies in the early phase of development; mesolevel institutional mechanisms to attain the industrial emergence settings; and, in pursuit of the virtuous cycle of development, the microlevel collaboration platform. We attribute the success of Taiwan's industrial system to this series of systematic government interventions. This study provides novel and salient normative principles that guide transformational policymakers in governing transitional processes of innovation system.